Oral versus pulse intravenous cyclophosphamide: a retrospective analysis of adverse events in a high infectious diseases burdened setting - Pretorius, Jan St Elmo (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2014.